PENGARUH PERTUMBUHAN EKONOMI TERHADAP PENDAPATAN ASLI DAERAH DI PROVINSI JAMBI - M. Zahari MS (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
Economic growth has always been one indicator of improving the welfare of the population of a region or country. Regional development as an integral part of national development is essentially an effort to increase the capacity of regional growth so as to run the government well.Local revenue is an important benchmark for determining the level of regon capacity in implementing real autonomy and responsibility. In the local government's efforts to increase revenue can not be separated from efforts to boost economic growth. Areas that positive economic growth can boost local revenue. This study aimed to analyze the influence of economic growth on local revenue in Jambi Province. Analyses were performed with a simple regression model. While the data used is the time series data for the period 2004 - 2013. The results of the analysis concludes that economic growth is significant and positive effect on local revenue in the province of Jambi.Keywords : Autonomy, Economic Growth, Local Revenue